Prevalence of asymptomatic sexually transmitted infections in HIV-positive men who have sex with men in Germany: results of a multicentre cross-sectional study. - Spinner, Christoph D.; Boesecke, Christoph; Jordan, Cornelius; Wyen, Christoph; Kümmerle, Tim; Knecht, Gaby; Scholten, Stefan; Zink, Alexander; Krznaric, Ivanka; Noe, Sebastian (Infection, 2018)
Purpose: Sexually transmitted infections (STIs) occur frequently in risk populations. Hereby, the role of screening-programmes remains controversial. Our study aimed to determine the prevalence of STI infections in HIV-positive men-who-have-sex-with-men (MSM).Methods: We enrolled asymptomatic, HIV-MSM in a prospective cross-sectional study from February to August 2016 at seven German HIV-centres. All subjects were screened for Treponema-pallidum (TP) and hepatitis-B/C-infection. HIV RNA and screening for oral, rectal and urethral colonisation by Chlamydia-trachomatis (CT) and/or Neisseria-gonorrhoeae (NG) was performed. All subjects were asked to complete a sexual-risk-behaviour-questionnaire.Results: In total, 296 subjects with a median age of 43.2 (36.2-49.5) years were enrolled; 99.3% were on ART for 5.5 (2.3-11.2) years. HIV RNA was < 50 copies/mL in 93.6%. Active syphilis infection was found in 5.0% of all patients, whereas 55.4% had history of infection. HCV seropositivity was found in 33 patients (13.2%) and positive HCV RNA was available in 39.4%. 66/294 (22.5%) showed negative anti-HBs-antibodies, indicating lack of immunity. Overall, 40/296 (13.5%) had positive CT/NG swabs (CT in 8.8%; 7.3% anorectal, 1.7% oropharyngeal, 1.0% urethral and NG in 6.8%; 4.5% anal, 2.0% oropharyngeal, 1.4% urethral). Time since HIV infection < 7 years (OR 2.6 (1.2-5.5); p = 0.012), the use of inhalative nitrites (“poppers”) (OR 2.8 (1.3-5.9; p = 0.008) and reporting unprotected intercourse with > 20 partners within the last 6 months [OR 3.0 (1.2-7.8); p = 0.003] were significantly associated in multivariate analysis.Conclusion: We found high numbers of asymptomatic syphilis, hepatitis-C and CT/NG infections in HIV-MSM, remarkably in patients with shorter duration of HIV-infection with more sexual partners within last 6 months.